Influência da densidade e espaçamento em duas cultivares de soja no manejo de Phakopsora pachyrhizi - Dahmer, Jonas (2016)
In the current situation, Brazil has cultivars with grain yield potential of 6000 kg.ha-1. However, due to a number of factors such as, plant spacing in the environment and management practices, productivity in the national average is around 3,000 kg.ha-1. Debortoli et al. (2006) point out that the most appropriate distribution of plants in the area provides greater retention and photosynthetic efficiency of the leaves, especially in the lower canopy due to the constant interception of radiation and penetration and fungicide coverage, reflecting productivity improvements. The objective is to evaluate the influence of row spacing for different plant densities in different soybean cultivars, the management of soybean rust. The need to obtain specific knowledge regarding the optimal arrangement of plants for each cultivar, justifies this work. The row spacings were 30, 45 and 60 cm, and the density was 150, 250 and 350 pl.ha-1 for each line spacing. These plants arrangements were made for two soybean cultivars. Each cultivar was a factorial experiment 3x3, totaling 18 treatments. The variables were: number of drops per cm2, percentage of coverage and water volume by water sensitive paper, area under the disease progress curve, yield components, in addition to grain yield (kg.ha-1). Smaller spacing and lower densities provided greater penetration drops. Cultivars showed different behavior in penetration drops. The highest densities had higher IAF. The AUDPC was higher in higher densities. The spacing of 30 cm was lower AACPD. The number of nodes per plant was higher in lower densities. Productivity was higher in lower densities. In NA 5909 RR spacing of 30 cm obtained higher productivity. Therefore, the increased spacing can be regarded as a practice of management for diseases since the number of plants is maintained straight.